Fast leak detection and location of gas pipelines based on an adaptive particle filter - Liu, Ming; Zang, Shu; Zhou, Donghua (Zielona Góra: Uniwersytet Zielonogórski)
Leak detection and location play an important role in the management of a pipeline system. Some model-based methods,such as those based on the extended Kalman filter (EKF) or based on the strong tracking filter (STF), have been presentedto solve this problem. But these methods need the nonlinear pipeline model to be linearized. Unfortunately, linearizedtransformations are only reliable if error propagation can be well approximated by a linear function, and this condition doesnot hold for a gas pipeline model.
Keywords: gas pipelines; leak detection and location; particle filter